2019
DOI: 10.1371/journal.pone.0212524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of explant size on epithelial outgrowth, thickness, stratification, ultrastructure and phenotype of cultured limbal epithelial cells

Abstract: PurposeTransplantation of limbal stem cells is a promising therapy for limbal stem cell deficiency. Limbal cells can be harvested from either a healthy part of the patient’s eye or the eye of a donor. Small explants are less likely to inflict injury to the donor site. We investigated the effects of limbal explant size on multiple characteristics known to be important for transplant function.MethodsHuman limbal epithelial cells were expanded from large versus small explants (3 versus 1 mm of the corneal circumf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
(107 reference statements)
1
10
1
Order By: Relevance
“…Moreover, the epithelial cell sheets developed from the limbal explants ex vivo showed greater integrity, as evident from the rich development of desmosomes, hemidesmosomes, and E-cadherins. 20,21 Furthermore, a study reported by Ekpo et al had cultured the cadaver tissues adjacent to the limbus, that is, toward corneal (L.cor) and conjunctival (L.conj) sides. Interestingly, they have noted that the cells cultured from the L.conj had more growth potential and stemness than L.cor, as evident from p63α expression.…”
Section: Limbal Epithelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the epithelial cell sheets developed from the limbal explants ex vivo showed greater integrity, as evident from the rich development of desmosomes, hemidesmosomes, and E-cadherins. 20,21 Furthermore, a study reported by Ekpo et al had cultured the cadaver tissues adjacent to the limbus, that is, toward corneal (L.cor) and conjunctival (L.conj) sides. Interestingly, they have noted that the cells cultured from the L.conj had more growth potential and stemness than L.cor, as evident from p63α expression.…”
Section: Limbal Epithelial Cellsmentioning
confidence: 99%
“…Moreover, the epithelial cell sheets developed from the limbal explants ex vivo showed greater integrity, as evident from the rich development of desmosomes, hemidesmosomes, and E‐cadherins. 20 , 21 …”
Section: Culture and Expansion Of Limbal‐derived Stem Cellsmentioning
confidence: 99%
“…Utheim et al reported that larger (3 mm) limbal explants yield larger outgrowths and are preferable than small (1 mm) explants, although small explant exhibited higher growth rates. No differences between small and large explants were detected when considering other parameters such as explant thickness, strength, and expression of stem cell markers [19]. The explant must be harvested from an area of the limbus that has a sufficient…”
Section: Plos Onementioning
confidence: 99%
“…Several groups have described the ideal size of a limbal explant that will yield the greatest degree of stemness in cell cultures [16][17][18][19]. In a recent study, stemness of explants from four different locations within the limbus, including superior, inferior, nasal, and temporal, were compared; the results indicated that the superior and inferior limbal areas exhibited greater growth potential [20].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry and RT-PCR have shown that cultured OMECs are positive for keratin (K)3, K4, and K13 [ 13 , 14 , 17 , 21 , 26 , 31 33 ], the latter is not expressed in the corneal epithelium [ 51 ]. OMECs also express markers of corneal differentiation connexin 43, laminin 5 [ 52 , 53 ], and putative stem cell markers ß1-integrin, p75, p63, ABCG2, C/EBPδ [ 52 , 54 ]. They do not express corneal-specific K12 and transcription factor PAX6 [ 22 , 31 ].…”
Section: Introductionmentioning
confidence: 99%